2022
DOI: 10.3390/ma15217713
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Compressive Strength of Concrete Containing Fly Ash and Rice Husk Ash Using ANN and GEP Models

Abstract: Climate change has become trending news due to its serious impacts on Earth. Initiatives are being taken to lessen the impact of climate change and mitigate it. Among the different initiatives, researchers are aiming to find suitable alternatives for cement. This study is a humble effort to effectively utilize industrial- and agricultural-waste-based pozzolanic materials in concrete to make it economical and environmentally friendly. For this purpose, a ternary blend of binders (i.e., cement, fly ash, and rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Meanwhile, ensemble models predicted CS more accurately than standalone models elsewhere [23][24][25][26].…”
Section: Machine Learning and Compressive Strength Predictionmentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile, ensemble models predicted CS more accurately than standalone models elsewhere [23][24][25][26].…”
Section: Machine Learning and Compressive Strength Predictionmentioning
confidence: 94%
“…A recent study utilized GEP (gene expression programming) and an ANN to estimate the compressive strength of recycled aggregate concrete [26]. The GEP model was reported to be more accurate in predicting the CS than the ANN model [30].…”
Section: Machine Learning and Compressive Strength Predictionmentioning
confidence: 99%
“…This value, according to them, was 16.1% higher in strength than the control samples. In their own work, Al-Hashem et al (2022) showed that ANN can be used to predict the 28-day strength of Rice husk ash (RHA) and Fly ash (FA) ternary blends in concrete. Alyami et al ( 2023) investigated the possibility of producing sustainable ultra-highperformance concrete using the ternary blends of rice husk ash and sugarcane leaf (SLA) ash.…”
Section: Ternary Blends Of Rice Husk Ash and Other Wastes In Concretementioning
confidence: 99%